Transforming Oil and Gas Operations with GIS: Insights from the Sonatrach SOD Project - Rachid Yassine AKKOUCHE; Kamel Boussafi (Journal of Excellence for Economics and Management Research, 2024)
This study examines the implementation and impact of Geographic Information Systems (GIS) in the oil and gas industry, focusing on the Smart Oil Data (SOD) project at Sonatrach, Algeria's national Oil and Gas company. As the energy sector undergoes rapid digital transformation, GIS has emerged as a tool for optimizing operations, enhancing decision-making, and addressing environmental concerns. The research employs a case study approach to analyze Sonatrach's experience with SOD, an integrated GIS solution built on ESRI's platform. The study investigates how GIS technologies are applied across the upstream, midstream, and downstream segments, and in Health, Safety, and Environment management. It also explores the challenges of implementing such a system, including data standardization, organizational change management, and integrating innovation and renewable energy initiatives. Findings show that the SOD project significantly improved Sonatrach's operational efficiency, data management, and strategic planning. However, the implementation underscored the need for robust change management strategies and continuous innovation.